PERAN KONTROL DIRI TERHADAP PERILAKU CYBERSLACKING PADA MAHASISWA - PUTRA, HOKI HERIYONO; R. DEWI, FRANSISCA IRIANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The phenomenon of cyberslacking in students during lectures is caused by inappropriate internet use. Cyberslacking is an act of using gadgets at inappropriate times such as opening social media during lectures or playing games while the lecturer is giving an explanation in class. One of the causal factors is weak self-control. Therefore, this study aims to test how much self-control contributes to cyberslacking behavior in students. The measures used were the Cyberslacking Academic Scale and the Brief Self-Control Scale (BSCS). A quantitative correlational approach was used in this study, using a convenience sampling data collection technique. Data were collected using a questionnaire constructed from a scale of 1 to 7 for the self-control measure and 1 to 5 for the cyberslacking measure. The study involved 232 students from public and private universities, with the majority of respondents from private universities (51.5%). In terms of gender, 66.4% of the respondents were female students. The results of the regression analysis showed that self-control plays a negative role in cyberslaking behaviour among university students. The results of the t-test = -14.233; p = 0.000 (.0.05). The study concluded that there is a role of self-control on cyberslacking behaviour in college students. With a contribution of 46.8%. While the remaining 53.2% is influenced by other factors. ABSTRAKFenomena cyberslacking pada mahasiswa selama perkuliahan disebabkan penggunaan internet yang tidak semestinya. Cyberslacking ialah suatu tindakan memakai gawai saat yang tidak tepat seperti membuka sosial media saat perkuliahan berlangsung atau bermain game saat dosen sedang memberikan penjelasan di kelas. Salah satu faktor penyebabnya ialah karena kontrol diri yang lemah. Untuk itu studi ini bertujuan menguji seberapa besar kontrol diiri berkontribusi menyebabkan terjadi perilaku cyberslacking pada mahasiswa. Alat ukur yang dipakai yaitu Cyberslacking Academic Scale dan The Brief Self-Control Scale (BSCS). Pendekatan kuantitatif korelasional diterapkan dalam studi ini, dengan menggunakan teknik pengumpulan data convinience sampling. Data dikumpulkan melalui kuesioner yang disusun dari skala 1 hingga 7 untuk alat ukur kontrol diri dan 1 hingga 5 untuk Cyberslacking. Studi ini melibatkan 232 mahasiswa perguruan tinggi negeri dan swasta mayoritas responden dari perguruan tinggi swasta (51.5%). Berdasarkan jender, responden mahasiswi yang terlibat sebesar 66,4%. Hasil analisis regresi memperlihatkan bahwa kontrol diri berperan secara negatif terhadap perilaku cyberslaking pada mahasiswa. Hasil uji t= -14.233; p=0.000 (,0.05). kesimpulan studi bahwa terdapat peran kontrol diri terhadap perilaku cyberslacking pada mahasiswa. Dengan kontribusi sebesar 46,8%. Sementara 53,2% lainnya dipengaruhi oleh faktor lain.